Selected Topics on Optical Amplifiers in Present Scenario - Kumar Garai, Sisir (IntechOpen, 2012)
With the explosion of information traffic, the role of optics becomes very significant to fulfill the demand of super fast computing and data processing and the role of optical amplifier is indispensable in optical communication field. This book covers different advance functionalities of optical amplifiers and their emerging applications such as the role of SOA in the next generation of optical access network, high speed switches, frequency encoded all-optical logic processors, optical packet switching architectures, microwave photonic system, etc. Technology of improving the gain and noise figure of EDFA and, the study of the variation of material gain of QD structure are also included. All the selected topics are very interesting, well organized and hope it will be of great value to the postgraduate students, academics and anyone seeking to understand the trends of optical amplifiers in present scenario.